A type of NO x Composite supports, catalysts, preparation methods and applications for synergistic removal of VOCs
Patent Information
- Application Number
- CN202310237401.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-03-14
AI Technical Summary
但是,该催化剂的起始温度活性窗口高且温度窗口较窄
(1)载体和活性组分的选择和制备是开发高效催化剂的先决条件,本发明采用的催化剂载体具有更大的比表面积、更强的表面酸碱性及更好的强度和热稳定性,这是由于复合载体不同组分边界处有大量的“异质结”,阻止了单一组分的团聚结晶。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental catalyst technology, and relates to a composite support, catalyst, preparation method and application for the synergistic removal of NOx and VOCs. Specifically, it relates to a composite support, catalyst, preparation method and application for the synergistic removal of NOx and VOCs in industrial waste gas. Background Technology
[0002] Catalytic technology is currently the mainstream control technology for denitrification and VOCs removal, and it is highly favored by the market due to its advantages such as high pollutant removal efficiency, high conversion efficiency, and good selectivity. Among them, ammonia selective catalytic reduction (NH3-SCR) technology is one of the most efficient technologies in the field of denitrification, and it is widely used in emission control of industrial waste gas emissions, municipal solid waste incineration, or vehicle exhaust. At the same time, SCR devices are often used for synergistic catalytic removal of NOx and VOCs, which can save process equipment construction space while significantly reducing pollution reduction costs, thereby achieving synergistic treatment and environmentally friendly treatment effects.
[0003] CN108993544A discloses a catalyst for removing NOx and VOCs from low-temperature, high-sulfur exhaust gas. This catalyst is a bifunctional catalyst based on a titanium-based nanotube support and an acidified perovskite active component. The catalyst is intended for the purification of low-temperature, high-sulfur ship exhaust gas, but its bifunctional removal performance for NOx and VOCs in complex industrial waste gases needs further improvement.
[0004] CN113000046A discloses a bifunctional catalyst based on modified manganese-based mullite. The catalyst primarily utilizes a hydrothermal method and surface acid etching to prepare metal-doped manganese-based mullite materials, followed by heat treatment to obtain nanoparticle catalysts. These catalysts exhibit high activity and stability in synergistic purification. However, the catalyst has a high onset temperature activity window and a relatively narrow temperature window.
[0005] In recent years, research on the synergistic removal of NOx and VOCs has been increasing, but the mechanisms and effects of their synergistic removal remain unclear. In particular, there is still great potential for developing bifunctional catalysts with wide temperature windows, high removal efficiency, high stability, and high resistance to water and sulfur for complex industrial waste gases. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a composite support, catalyst, preparation method, and application for the synergistic removal of NOx and VOCs. The catalyst exhibits advantages such as a wide temperature window, high removal efficiency, and high stability when used to treat industrial waste gas.
[0007] The first aspect of this invention is to provide a composite carrier for the synergistic removal of NOx and VOCs, wherein the composite carrier is a titanium-zirconium-silicon modified molecular sieve composite carrier, comprising a silica-modified molecular sieve, zirconium dioxide, and titanium dioxide, wherein the zirconium dioxide and titanium dioxide are loaded on the surface of the silica-modified molecular sieve; the molecular sieve used in the silica-modified molecular sieve is one or more of ZSM-5, SSZ-13, and Y-type molecular sieves, preferably ZSM-5 molecular sieve; the molar ratio of titanium dioxide to zirconium dioxide in the composite carrier is 1 to 15, preferably 2 to 9; the mass ratio of the total mass of titanium dioxide and zirconium dioxide to the mass of the silica-modified molecular sieve is 1 to 7, preferably 1 to 5.
[0008] Furthermore, in the above-mentioned composite carrier, the specific surface area of the composite carrier is 100-130 m². 2 / g; pore volume is 0.15~0.25mL / g; pore size distribution range is 5~20nm, average pore size is 9.0~11.5nm, of which 5~10nm mesopore volume accounts for 65%~80% of the total pore volume; total acid content is 0.35~0.45mmol / g.
[0009] A second aspect of this invention is to provide a method for preparing a composite carrier for the synergistic removal of NOx and VOCs, the method comprising the following steps: (1) The molecular sieve is modified by silanization; (2) Introduce titanium source and zirconium source into the silica-modified molecular sieve obtained after step (1), and after drying and calcination, obtain the final composite carrier for the synergistic removal of NOx and VOCs.
[0010] Furthermore, in step (1) of the above method, the molecular sieve is one or more of ZSM-5, SSZ-13, and Y-type molecular sieves, preferably ZSM-5 molecular sieve.
[0011] Furthermore, in step (1) of the above method, the silanization modification treatment uses one or more of trimethylchlorosilane, tetramethylsilane, tetraethoxysilane, and dimethyldichlorosilane.
[0012] Further, in step (1) of the above method, the molecular sieve undergoes silanization modification treatment using vapor deposition. The specific process of the vapor deposition method is as follows: the molecular sieve powder is calcined to remove physicochemically adsorbed water; then it is uniformly mixed with a silanization modification reagent and transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene for reaction; the mass ratio of the molecular sieve powder to the silanization modification reagent is 2-5; the reaction temperature is 110-130℃, and the reaction time is 3-12h; after the reaction is completed, the sample is allowed to cool naturally to room temperature, the solid product is filtered and recovered, washed 3-6 times with toluene or acetone, and then dried at a temperature of 70-90℃ for 10-15h to obtain silica-modified molecular sieve.
[0013] Furthermore, in step (2) of the above method, the titanium source and zirconium source can be introduced into the silica-modified molecular sieve obtained after step (1) by impregnation method. The titanium source and zirconium source can be introduced separately or simultaneously.
[0014] Further, in step (2) of the above method, the process of introducing titanium and zirconium sources into the silica-modified molecular sieve obtained after step (1) is as follows: the titanium source is one or more of tetrabutyl titanate, titanium tetrachloride, and titanium nitrate, preferably tetrabutyl titanate; the zirconium source is one or more of zirconium oxychloride octahydrate, zirconium tetrachloride, and zirconium nitrate, preferably zirconium oxychloride octahydrate; the titanium source is slowly added dropwise to anhydrous ethanol, and then stirred to obtain a mixed solution for 30-60 min; the zirconium source and silica-modified molecular sieve powder are added to the mixed solution, and distilled water and concentrated hydrochloric acid are slowly added dropwise, and stirred until a gel is formed; the gel is dried and calcined to obtain a composite carrier for the synergistic removal of NOx and VOCs. Among them, the molar ratio of titanium to zirconium in the titanium source and the zirconium source is 1-15; the total mass ratio of the titanium source and the zirconium source to the silica-modified molecular sieve is 2-15; the volume ratio of distilled water and concentrated hydrochloric acid to ethanol is 0.05-0.2.
[0015] Furthermore, in step (2) of the above method, the drying time is 5-10 hours, the drying temperature is 100-130°C, preferably 6-8 hours, and the drying temperature is 110-120°C; the calcination temperature is 350-550°C, and the calcination time is 4-7 hours, preferably 450-500°C, and the calcination time is 4-5 hours.
[0016] A third aspect of the present invention is to provide a catalyst for the synergistic removal of NOx and VOCs, the catalyst comprising the aforementioned composite support and an active metal component; the active metal component comprising d-block transition metal elements and lanthanide metal elements, wherein the d-block transition metal elements comprise at least one of V, W, and Mn; and the lanthanide metals comprise at least one of Pr, Ce, and Sm; based on the weight of the composite support, the content of the d-block transition metals, calculated as metal oxides, is 10–40%, and the content of the lanthanide metals, calculated as metal oxides, is 2–10%.
[0017] The fourth aspect of this invention is to provide a method for preparing a catalyst for the synergistic removal of NOx and VOCs, the method comprising the following steps: introducing d-block transition metals and lanthanide metal elements onto the composite support described above, and obtaining the final catalyst for the synergistic removal of NOx and VOCs after drying and calcination.
[0018] Furthermore, in the preparation process of the catalyst of the present invention, the d-block transition metal and lanthanide metal elements on the composite support can be introduced separately or simultaneously, and there is no particular requirement for the order of introduction during the separate introduction process.
[0019] Furthermore, in the preparation process of the catalyst of the present invention, the introduction of transition metals and lanthanide metal elements on the composite support is carried out as follows: 1) Dissolve d-block transition metal oxides and lanthanide metal oxide powders in dilute nitric acid solution to obtain a suspension of active components; 2) Slowly place the composite carrier powder into the suspension of active components obtained in step 1) and stir; slowly dry the suspension and calcine it to obtain the final catalyst for the synergistic removal of NOx and VOCs.
[0020] Further, in step 1), the transition metal oxide is one or more of V2O5, WO3, MnO2, and Fe2O3, preferably V2O5 and / or WO3; the lanthanide metal oxide is one or more of PrOx, NdOx, CeOx, and SmOx, preferably CeOx and / or SmOx.
[0021] Further, in step 2), when drying the suspension, the temperature is 100–160℃ and the drying time is 20–60 h; during calcination, the calcination time is 4–40 h and the heating rate is 1–20℃ / min. The specific calcination method is as follows: the temperature is first increased from room temperature to 400–600℃ at a rate of 1–20℃ / min, and then held at 400–600℃ for 2–9 h. After calcination, the temperature is slowly reduced to room temperature to obtain the catalyst finally used for the synergistic removal of NOx and VOCs.
[0022] A fifth aspect of the present invention is to provide a method for synergistic removal of NOx and VOCs, the method employing the catalyst described above.
[0023] Furthermore, in the above-mentioned method for synergistic removal of NOx and VOCs, the specific operating conditions are as follows: the raw material is industrial waste gas, and the reaction temperature range is 200–350°C.
[0024] Furthermore, in the above-mentioned method for synergistic removal of NOx and VOCs, the composition of the industrial waste gas is as follows: NO and NH3 concentrations of 500–1000 μL / L, chlorobenzene concentration of 100–200 μL / L, O2 content of 3% (v / v), H2O content of 5–20% (v / v), NH3 / NO ratio of 1:0.5–1.5 (molar ratio), and volumetric hourly space velocity of 3000–8000 h⁻¹. -1 .
[0025] Compared with existing technologies, the present invention provides a composite support, catalyst, preparation method, and application for the synergistic removal of NOx and VOCs, which has the following advantages: (1) The selection and preparation of the support and active components are prerequisites for the development of efficient catalysts. The catalyst support used in this invention has a larger specific surface area, stronger surface acidity and alkalinity, and better strength and thermal stability. This is because there are a large number of "heterogeneous junctions" at the boundaries of different components of the composite support, which prevents the agglomeration and crystallization of single components.
[0026] (2) The results show that for the adsorption and catalytic oxidation of VOCs, the hydrophobically modified molecular sieve not only has a very uniform and controllable pore structure, but also reduces its hydrophilicity, which is very beneficial to the selective adsorption of VOCs molecules. In particular, when the molecular sieve is combined with active metal, it can improve the catalytic oxidation performance of VOCs and enhance the synergistic treatment effect.
[0027] (3) This invention simultaneously loads d-block transition metal and lanthanide metal active components onto a titanium-zirconium-silicon modified molecular sieve composite support to prepare a bifunctional catalyst for removing NOx and VOCs under medium and low temperature conditions. The catalyst support has the characteristics of large specific surface area, strong acidity, strong hydrophobicity, excellent adsorption performance and good hydrothermal stability; the active components not only have the characteristics of efficient catalytic oxidation of NOx and VOCs, but their interaction can also stabilize the overall structure of the catalyst, promote ion exchange, and activate the redox reaction, thereby significantly improving the removal rate of NOx and VOCs under low, medium and high temperature conditions. Importantly, this catalyst has significant advantages such as high activity, wide temperature window, large surface area and good hydrophobicity, which can effectively make up for the disadvantages of existing bifunctional catalysts, such as narrow temperature window or low conversion efficiency.
[0028] (4) The preparation method of the present invention is simple, fast, and low in cost. It can be mass-produced and can be widely used for the synergistic removal of NOx and VOCs from high SO2 and high NOx waste gases emitted in petrochemical processes. Implementation
[0029] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0030] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art. Unless otherwise specified, the experimental materials used in Example 1 were purchased from conventional biochemical reagent stores.
[0031] Example 1 The preparation of a composite support for the synergistic removal of NOx and VOCs includes the following steps: (1) Silanization modification of molecular sieve: Weigh 3g of ZSM-5 molecular sieve powder, calcine to remove physicochemically adsorbed water; then mix it evenly with 1g of trimethylchlorosilane, transfer it to a stainless steel high-pressure reactor lined with polytetrafluoroethylene for reaction, the reaction temperature is 120℃, the reaction time is 6h; after the reaction is completed, allow the sample to cool naturally to room temperature, filter and recover the solid product: wash it 3 times with toluene, and then dry it at 80℃ for 12h to obtain silica-modified molecular sieve.
[0032] (2) Preparation of composite carrier material: Weigh 27 mL of tetrabutyl titanate and slowly add it dropwise to 40 mL of anhydrous ethanol, stirring for 30 min; add 9 g of zirconium oxychloride powder octahydrate and silica-modified molecular sieve powder to the solution, slowly add 6 mL of distilled water and a small amount of concentrated hydrochloric acid, stirring until a gel is formed; dry the gel and calcine it to form composite carrier S1. The drying time was 6 h and the drying temperature was 120 °C. The calcination time was 8 h and the calcination temperature was 500 °C. The specific calcination method in the muffle furnace was as follows: the temperature was first increased from room temperature to 500 °C at a rate of 5 °C / min, and then kept constant at 500 °C for 4 h. After calcination, the temperature was slowly reduced to room temperature. Thus, composite carrier S1 was obtained.
[0033] Example 2 The basic steps are basically the same as in Example 1, except that in step (1), the amount of ZSM-5 molecular sieve powder weighed is changed to 3.6g, while the other conditions remain unchanged. Thus, the composite carrier S2 is obtained.
[0034] Example 3 The basic steps are basically the same as in Example 1, except that in step (1), the amount of ZSM-5 molecular sieve powder weighed is changed to 6g, while the other conditions remain unchanged. Thus, the composite carrier S3 is obtained.
[0035] Example 4 The basic steps are basically the same as in Example 1, except that in step (2) the composite carrier material is prepared by slowly adding 30 mL of tetrabutyl titanate to 40 mL of anhydrous ethanol and stirring for 30 min; then adding 6 g of zirconium oxychloride powder octahydrate and silica-modified molecular sieve powder to the solution, with the other conditions remaining unchanged. Thus, composite carrier S4 is obtained.
[0036] Example 5 The basic steps are basically the same as in Example 1, except that in step (2) the composite carrier material is prepared by slowly adding 32 mL of tetrabutyl titanate to 40 mL of anhydrous ethanol and stirring for 30 min; then adding 4 g of zirconium oxychloride powder and silica-modified molecular sieve powder to the solution, with the other conditions remaining unchanged. Thus, the composite carrier S5 is obtained.
[0037] Example 6 The basic steps are basically the same as in Example 1, except for the modification process of ZSM-5 molecular sieve in step (1). 3g of ZSM-5 molecular sieve powder was weighed and calcined to remove physicochemically adsorbed water; then it was mixed evenly with 1g of tetraethoxysilane and transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene for reaction at a temperature of 120℃ for 8h; after the reaction was completed, the sample was allowed to cool naturally to room temperature, and the solid product was filtered and recovered: washed 6 times with toluene, and then dried at a temperature of 70℃ for 15h to obtain silica-modified molecular sieve. After composite, the carrier S6 was obtained.
[0038] Comparative Example 1 Step (1) of silanizing the molecular sieve is omitted; otherwise, the process is the same as in Example 1. Thus, the composite carrier DS1 is obtained.
[0039] Comparative Example 2 In step (2), 36g of zirconium salt was weighed and added to anhydrous ethanol to prepare the carrier, resulting in a zirconium-silicon modified molecular sieve composite carrier. The rest of the process was the same as in Example 1. Thus, the composite carrier DS2 was obtained.
[0040] Comparative Example 3 In step (2), 36 mL of tetrabutyl titanate was weighed and added to anhydrous ethanol to prepare the carrier, thus obtaining the titanium-silicon modified molecular sieve composite carrier. The rest is the same as in Example 1. Thus, the composite carrier DS3 is obtained.
[0041] The physicochemical properties of the composite carriers obtained in the above embodiments and comparative examples are shown in Table 1 below.
[0042] Table 1. Physicochemical properties of composite carriers
[0043] Example 7 The preparation of a catalyst for the synergistic removal of NOx and VOCs includes the following steps: Preparation of active component suspension: Pour 100 mL of dilute nitric acid into a 250 mL beaker, and add d-block transition metal oxide and lanthanide metal oxide in sequence; Catalyst preparation: Composite support S1 powder was slowly added to the active component suspension and stirred; the suspension was then dried and calcined. The drying time was 40 hours at 100°C. The calcination time was 5 hours at 450°C. The specific calcination method in the muffle furnace was as follows: the temperature was increased from room temperature to 500°C at a rate of 5°C / min, held at 500°C for 4 hours, and then slowly reduced to room temperature after calcination. Catalyst C1 was finally obtained. Catalysts C2, C3, C4, C5, C6, DC1, DC2, and DC3 were prepared using S2, S3, S4, S5, S6, DS1, DS2, and DS3, respectively.
[0044] The catalyst compositions obtained in the above examples and comparative examples are shown in Table 2 below.
[0045] Table 2. Percentage of catalyst composition
[0046] The denitrification catalysts prepared in the examples and comparative examples were evaluated. The evaluation was conducted on a small-scale laboratory apparatus under the following conditions: NO and NH3 concentrations of 750 μL / L, chlorobenzene concentration of 150 μL / L, O2 content of 3% (v / v), H2O content of 10% (v / v), NH3 / NO molar ratio of 1:1, and volume hourly space velocity of 4000 h⁻¹. -1 To eliminate the influence of surface adsorption, data collection and testing were started 20-30 minutes after the system had been running stably under ventilation.
[0047] The catalytic activity of the catalyst is reflected by the denitrification activity of NO, which is calculated by the following formula: Denitrification activity = [(C0-C) / C0]×100%.
[0048] In the formula, C0 is the initial NO concentration, and C is the NO concentration in the treated gas.
[0049] The removal efficiencies of NO and chlorobenzene by different catalysts at different temperatures are shown in Tables 3 and 4, respectively.
[0050] Table 3. Denitrification rate at different temperatures
[0051] Table 4. VOCs removal rate at different temperatures
Claims
1. A catalyst for the synergistic removal of NOx and VOCs, the catalyst comprising a composite support and an active metal component, wherein the composite support is a titanium-zirconium-silicon modified molecular sieve composite support, the titanium-zirconium-silicon modified molecular sieve composite support comprising a silica-modified molecular sieve, zirconium dioxide, and titanium dioxide, wherein the zirconium dioxide and titanium dioxide are supported on the surface of the silica-modified molecular sieve; the molecular sieve used in the silica-modified molecular sieve is one or more of ZSM-5, SSZ-13, and Y-type molecular sieves; the molar ratio of titanium dioxide to zirconium dioxide in the composite support is 1 to 9, and the mass ratio of the total mass of titanium dioxide and zirconium dioxide to the mass of the silica-modified molecular sieve is 1 to 7; The active metal component includes d-block transition metal elements and lanthanide metal elements. The d-block transition metal elements include at least one of V, W, and Mn, and the lanthanide metals include Ce and Sm. Based on the weight of the composite carrier, the content of the d-block transition metals, calculated as metal oxides, is 10% to 40%, and the content of the lanthanide metals, calculated as metal oxides, is 2% to 10%. The composite carrier has a specific surface area of 100–130 m². 2 / g; pore volume is 0.15~0.25mL / g; pore size distribution range is 5~20nm, average pore size is 9.0~11.5nm, of which 5~10nm mesopore volume accounts for 65%~80% of the total pore volume; total acid content is 0.35~0.45mmol / g; The silica-modified molecular sieve is prepared by vapor deposition using a silanization modifying agent, wherein the silanization modifying agent is one or more of trimethylchlorosilane, tetramethylsilane, tetraethoxysilane, and dimethyldichlorosilane.
2. The catalyst according to claim 1, characterized in that: The molecular sieve used was ZSM-5.
3. The catalyst according to claim 1, characterized in that: The molar ratio of titanium dioxide to zirconium dioxide in the composite carrier is 2 to 9; the total mass of titanium dioxide and zirconium dioxide is 1 to 5 times the mass ratio of the silica-modified molecular sieve.
4. The catalyst according to any one of claims 1-3, characterized in that: The preparation method of the composite carrier includes the following steps: (1) The molecular sieve is modified by silanization; (2) Introduce titanium source and zirconium source into the silica-modified molecular sieve obtained after step (1), and after drying and calcination, obtain the final composite carrier for the synergistic removal of NOx and VOCs.
5. The catalyst according to claim 4, characterized in that: The specific process of the vapor deposition method is as follows: molecular sieve powder is calcined to remove physicochemically adsorbed water; then it is uniformly mixed with silanization modification reagent and transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene for reaction; the mass ratio of molecular sieve powder to silanization modification reagent is 2-5. The reaction temperature is 110–130℃ and the reaction time is 3–12 h. After the reaction is completed, the sample is allowed to cool naturally to room temperature. The solid product is filtered and recovered, washed 3–6 times with toluene or acetone, and then dried at 70–90℃ for 10–15 h to obtain silica-modified molecular sieve.
6. The catalyst according to claim 4, characterized in that: In step (2), the titanium source and zirconium source are introduced into the silica-modified molecular sieve obtained after step (1) by impregnation. The titanium source and zirconium source are introduced separately or simultaneously.
7. The catalyst according to claim 4, characterized in that: In step (2), the process of introducing titanium and zirconium sources into the silica-modified molecular sieve obtained after step (1) is as follows: the titanium source is slowly added dropwise to anhydrous ethanol and then stirred to obtain a mixed solution for 30-60 minutes; the zirconium source and silica-modified molecular sieve powder are added to the mixed solution, and distilled water and concentrated hydrochloric acid are slowly added dropwise and stirred until a gel is formed; the gel is dried and calcined to obtain a composite carrier for the synergistic removal of NOx and VOCs.
8. The catalyst according to claim 4, characterized in that: In step (2), the drying time is 5 to 10 hours and the drying temperature is 100 to 130°C; the calcination temperature is 350 to 550°C and the calcination time is 4 to 7 hours.
9. The catalyst according to claim 8, characterized in that: In step (2), the drying time is 6-8 hours and the drying temperature is 110-120℃; the calcination temperature is 450-500℃ and the calcination time is 4-5 hours.
10. A method for preparing the catalyst according to any one of claims 1-9, characterized in that: The method includes the following steps: introducing d-block transition metals and lanthanide metals onto a composite support, followed by drying and calcination to obtain the final catalyst for the synergistic removal of NOx and VOCs.
11. The method according to claim 10, characterized in that: The d-block transition metals and lanthanide metals are introduced into the composite support, either separately or simultaneously.
12. The method according to claim 11, characterized in that: The process of introducing transition metals and lanthanides onto the composite support is as follows: 1) Dissolve d-block transition metal oxides and lanthanide metal oxide powders in dilute nitric acid solution to obtain a suspension of active components; 2) Slowly place the composite carrier powder into the suspension of active components obtained in step 1) and stir; slowly dry the suspension and calcine it to obtain the final catalyst for the synergistic removal of NOx and VOCs.
13. The method according to claim 12, characterized in that: In step 1), the transition metal oxide is one or more of V2O5, WO3, and MnO2, and the lanthanide metal oxide is CeOx and SmOx.
14. The method according to claim 13, characterized in that: In step 1), the transition metal oxide is V2O5 and / or WO3.
15. The method according to claim 12, characterized in that: In step 2), when drying the suspension, the temperature is 100–160℃ and the drying time is 20–60 h; when calcining, the calcination time is 4–40 h and the heating rate is 1–20℃ / min; the specific calcination method is as follows: the heating program first raises the temperature from room temperature to 400–600℃ at a rate of 1–20℃ / min, and then holds the temperature at 400–600℃ for 2–9 h. After calcination, the temperature is slowly lowered to room temperature to obtain the catalyst finally used for the synergistic removal of NOx and VOCs.
16. A method for synergistic removal of NOx and VOCs, characterized in that: The method uses the catalyst described in any one of claims 1-9 or the catalyst prepared by the method described in any one of claims 10-15 to synergistically remove NOx and VOCs from the feedstock.
17. The method according to claim 16, characterized in that: The raw material is industrial waste gas, and the reaction temperature range is 200-350℃.
18. The method according to claim 17, characterized in that: The composition of the industrial waste gas is as follows: NO and NH3 concentrations of 500–1000 μL / L, chlorobenzene concentration of 100–200 μL / L, O2 volume content of 3%, H2O volume content of 5–20%, NH3 / NO molar ratio of 1:0.5–1.5, and volume hourly space velocity of 3000–8000 h⁻¹. -1 .
Citation Information
Patent Citations
Catalyst for removing NOx and VOCs in low-temperature and high-sulfur tail gas as well as preparation method and application of catalyst
CN108993544A
Modified manganese-based mullite type catalyst for synergistic purification of nitrogen oxides and volatile organic compounds as well as preparation method and application of modified manganese-based mullite type catalyst
CN113000046A
Silicon-modified ZSM-35 molecular sieve preparation method
CN110624601A
High-temperature flue gas denitration catalyst and preparation method thereof
CN111346670A